2021
DOI: 10.7819/rbgn.v23i1.4092
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between brand Facebook page characteristics, perceived value, and customer engagement behavior: An application of Stimulus-Organism-Response (S-O-R)

Abstract: Purpose -With the advancement of technology and increased use of social media, brands have become part of the virtual world and try to grab customers' attention. Brand pages enable the consumer to voluntarily participate in providing feedback and ideas and to collaborate with others. This adds value to the firm. This research explores which characteristics help clothing brands to influence consumers into responding in the form of feedback, collaboration, and mobilization.Design/methodology/approach -Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…To the best of the authors' knowledge, this is the first work to analyze the keys to the success of influencer marketing on TikTok, and the behavioral responses of followers. The study also examines the extent to which the relationships established in other social networks are valid for TikTok (Arif et al, 2020;Aslam and Luna, 2021;Casaló et al, 2020) and proposes an integration of the SOR model and ELM to better explain followers' reactions toward influencer marketing on this new channel. In particular, it reveals that the peripheral route (via humor and hedonic experience) plays an important role in the persuasion of followers on TikTok.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors' knowledge, this is the first work to analyze the keys to the success of influencer marketing on TikTok, and the behavioral responses of followers. The study also examines the extent to which the relationships established in other social networks are valid for TikTok (Arif et al, 2020;Aslam and Luna, 2021;Casaló et al, 2020) and proposes an integration of the SOR model and ELM to better explain followers' reactions toward influencer marketing on this new channel. In particular, it reveals that the peripheral route (via humor and hedonic experience) plays an important role in the persuasion of followers on TikTok.…”
Section: Discussionmentioning
confidence: 99%
“…, 2018). Secondly, the S-O-R theory helps to predict the role of street food features and customer behaviour by offering a visual framework for exploring how environmental stimuli influence consumers' internal psychological reactions, thus shaping their behavioural responses (Aslam and de Luna, 2021). Consequently, we adopt the S–O–R theory as our research framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research of Zhang and Benyoucef [ 125 ] pointed out that in the research of consumer purchasing decisions, although the research based on the SOR has verified many antecedents that affect consumers’ purchasing decisions, the research of this theory has not identified the key factors. Although Aslam and Luna [ 3 ] pointed out in research on brand Facebook page characteristics on consumer engagement behavior, customer contact quality only affects brand learning value, which promotes consumer engagement behavior. However, the aforementioned conclusions can only show that customer contact quality has a certain uniqueness in the effect, and cannot explain its criticality, because content quality will also affect the brand learning value and affect the hedonic value.…”
Section: Theoretical Contribution and Practical Implicationmentioning
confidence: 99%